Clustering and Trends of Professional Audit Judgment: A Bibliometric Approach - Rifqi Aziz Pratama (Universitas Batanghari Jambi, 2026)
This study aims to answer three main questions: (1) how have the main developments and trends in the literature related to professional audit judgment changed over time; (2) what are the characteristics, scientific contributions, and most influential documents in the literature on professional audit judgment; and (3) what are the main themes, relationships between topics, and conceptual developments in professional audit judgment research based on co-occurrence network analysis and thematic mapping. Bibliometric methods were applied to 310 Scopus-indexed publications, and visual mapping was performed using Bibliometrix in RStudio. The results of this study indicate that professional skepticism, audit quality, and auditor behavior are core themes, while earnings management is the dominant basic theme. Themes such as CSR disclosure, assurance, and ethical judgment developed as motor themes, while key audit matters, COSO, and blockchain were niche themes. Issues such as big data, data analytics, and internal auditing emerged as emerging themes. These findings provide a comprehensive picture of the direction of conceptual development and opportunities for interdisciplinary research in the future.